Morbid obesity and use of second generation antipsychotics among adolescents in foster care: Evidence from Medicaid. (August 2016) - Allaire, Benjamin T.; Raghavan, Ramesh; Brown, Derek S.
Abstract: Background: Many adolescents enter foster care with high body mass index (BMI), and patterns of treatment further exacerbate the risk of morbid obesity. A principal risk factor for such exacerbation is the use of second generation antipsychotics (SGAs). We examine the association between receiving a morbid obesity diagnosis and SGA prescriptions among adolescents in foster care. Methods: We analyzed claims from 36 states' Medicaid Analytic Extract (MAX) files for 2000 through 2003. Obesity diagnoses were ascertained through a primary or secondary diagnosis claim of morbid obesity. Covariates included gender, race/ethnicity. Age, insurance status, state obesity rate, and state fixed effects. We calculated relative risks of a diagnosis based upon four SGAs (clozapine, olanzapine, quetiapine, and risperidone) associated with obesity and a polypharmacy indicator. Results: Of the 1, 261, 806 foster care adolescent-years in the MAX files, 6517 were diagnosed with morbid obesity, an annual prevalence of 0.5%. The risk of a morbid obesity diagnosis is much higher for female and non-white adolescents. The risk increases with age. Quetiapine and clozapine increased the risk of a morbid obesity diagnosis more than 2.5 times, and two or more psychotropic drugs (polypharmacy) increased the risk fivefold. Conclusions: Adolescents in foster care are much more likely to be on SGA medications, and therefore may be more susceptible to weight gain and obesity. Given that SGA prescribing for younger populations has only expanded since these data were released, our study may actually understate the magnitude of the problem. Care is needed when prescribing SGAs for foster care adolescents. Highlights: Foster care adolescents are at an increased risk of morbid obesity and for second generation antipsychotic (SGA) use. Medicaid claims files were examined. Risk of morbid obesity diagnosis higher for female, non-white, older adolescents Quetiapine and clozapine associated with a morbid obesity risk increase of more than 2.5 times. Two or more SGAs raised the risk for a morbid obesity diagnosis fivefold.